The Effect Of Virtual Reality In Electronic Worksheets With Discovery Learning On Improving Critical Thinking Skills Of Junior High School Students - Fahrezy, M.; Widowati, Asri; Winarto, Winarto; Rahmawati, Laifa (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
One of the important skills in the 21st century is critical thinking skills, as educational objectives focus on development to face the challenges of the world of education. This study aims to analyze the impact of using virtual reality in electronic worksheets with discovery learning on critical thinking skills of junior high school students. This research is an experimental research with a quantitative approach using Quasi-Experiment. The research design used Nonequivalent Control Group Design with two sample classes totaling 32 experimental and 32 control class students. Data collection on the level of critical thinking skills is seen from the results of pretest and posttest essays of 6 items on solar system material on 6 aspects of critical thinking skills i.e. analysis, evaluation, interpretation, inference, explanation, and metacognition. Data analysis was carried out Independent Sample T-Test test and effect size test. The results of this study indicate that there are differences in the critical thinking skills of junior high school students who use virtual reality in electronic worksheets with discovery learning and the use of virtual reality in electronic worksheets with discovery learning on students' critical thinking skills has a very strong influence.